Cladding Modified with PANI‐Oxalic Acid Composite Glucose Oxidase Immobilized Fiber Optic Intrinsic Glucose Biosensor. Issue 1 (22nd April 2016) - Pahurkar, Vikas; Dagdale, Shivaji; Tamgadge, Yuoraj; Nagale, Vinod; Muley, Gajanan
Summary: Polyaniline (PANI) and its composites have drawn considerable interest because of their economical importance, good environmental stability and satisfactory conductivity among the conductive polymers. Polymers are playing an increasingly important role in the development of biosensors. The use of conducting polymer composites for the construction of biosensor is increasing nowadays for the immobilization of biomolecules as it enhances the activity and performance of the sensor. In the present investigation, we have used PANI‐oxalic acid (OA) for the cladding modification to prepare fiber optic intrinsic glucose biosensor (FOIGB) for detection of glucose. PANI‐OA composite have shown good binding toward enzyme‐glucose oxidase (GOx) and high biological activity that results in enhanced sensing characteristics. This investigation highlights approach to synthesize PANI‐OA composite and its applications in cladding modified FOIB technology. The characterizations were made using X‐ray diffraction and scanning electron microscopy (SEM) techniques. The results revealed the formation of homogeneous, PANI‐OA film on sensing element. The sensing response of FOIGB toward glucose was measured by monitoring variation in power with varying glucose concentration.